2015
DOI: 10.1186/s12978-015-0073-0
|View full text |Cite
|
Sign up to set email alerts
|

Demand for long acting contraceptive methods among married HIV positive women attending care at public health facilities at Bahir Dar City, Northwest Ethiopia

Abstract: BackgroundThe use of long acting contraceptive methods (LACMs) is one of the strategies for preventing mother-to-child transmission (MTCT) of HIV. Studies noted that significant proportion of unintended pregnancy among HIV positive women was due to contraceptive failure mainly of short term contraceptives. This highlights the need to use most effective types of modern contraception, long acting contraceptive. However, studies conducted on demand for long acting contraceptive methods in this particular group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…The regional and national estimate of modern contraceptive was from the general population where as our estimate was from HIV positive women who were on HAART. Previous studies revealed that modern contraceptive utilization is relatively higher among HIV positive women as compared to the general population [32]. Our finding is also higher than other studies conducted in various parts of Ethiopia such as Debremarkos (47.9%) and Northern Tigray (44.3%).…”
Section: Discussioncontrasting
confidence: 56%
“…The regional and national estimate of modern contraceptive was from the general population where as our estimate was from HIV positive women who were on HAART. Previous studies revealed that modern contraceptive utilization is relatively higher among HIV positive women as compared to the general population [32]. Our finding is also higher than other studies conducted in various parts of Ethiopia such as Debremarkos (47.9%) and Northern Tigray (44.3%).…”
Section: Discussioncontrasting
confidence: 56%
“…Respondents who have children > 2 have 1.6 times greater chance of using Long Term Contraception than respondents who have ≤ two children to use Long Term Contraception. The results of this study were supported by research conducted in Bahir Dar City and Amhara District indicated that women of infertile age who had children> 2 were more likely to use long-term contraception [14,15], while in the study in Goba City showed no effect Number of children to use Long Term Contraception [4]. This is due to differences in location from data collection in urban and rural areas and the influence of communities in the environment.…”
Section: Discussionsupporting
confidence: 69%
“…David W. Hosmer and Stanley Lemeshow in their second edition book entitled "Applied Logistic Regression" recommended using a P-value of less than 0.25 as a screening criterion for variable selection for the multivariable analysis [39]. Other published articles used a p-value of 0.2 as a cut-off point to select variables for the multivariable analysis [40][41][42][43]. Therefore, in this study, variables having P-value ≤0.25 in the bivariate analysis were considered for multivariable analysis.…”
Section: Data Processing and Analysismentioning
confidence: 99%